Breaking wave loads and y+ value on offshore wind turbine monopiles - Chatzimarkou, E.; Michailides, Constantine; Onoufriou, Toula (My University, 2020)
Offshore monopiles are exposed to extremely transient hydrodynamic loads during the wave breaking process and the required analysis to capture those loads is highly demanding and complex. The structural integrity of the monopiles is affected by the nonlinear wave breaking loads. The answer to capture those nonlinear hydrodynamic loads and address those challenges relies on the use of a well-validated numerical model based on Computational Fluid Dynamics (CFD). One parameter crucial for the correct use of the numerical model is the y+ value, a non-dimensional distance, which indicates where the first cell is located near-wall region. The purpose of this paper is to investigate and present the distributions of the y+ value for different mesh configurations of a fixed bottom monopile subjected to breaking waves inside a numerical wave tank developed with the use of the open-access CFD code OpenFOAM. Reynolds-Averaged Navier-Stokes modeling is performed by applying the k-ω SST model and relevant results derived.